Analisis Framing Terhadap Pemberitaan Isu Presiden Tiga Periode Pada Portal Media Online Kompas.Com Dan Republika.Co.Id - Ari Jalul Hakam; Novi Budiman (Politik Islam, 2022)
This journal focuses on the framing of news on the issue of the Three-Term Presidential Discourse, with the aim of seeing and criticizing the framing of news on the Online Media Portal Kompas.com and Republika.co.id the March 2002 Issue. The research method in this study is to use a constructivism approach and the type of framing analysis research of Zhongdang Pan and Gerald M. Kosicki with four framing devices, namely syntax, script, thematic, and rhetorical. The results of the study concluded that, the framing carried out by the Kompas.com on news about the issue of the Three-Term Presidential Discourse, namely Kompas.com tried to position itself as a media that maintained objectivity in writing news on the issue of the Three-Term Presidential Discourse, although there was still a slight tendency to Kompas.com in giving more portion to the sources against the three-Term President, while the framing carried out Republika.co.id namely, Republika.co.id clearly leads readers to interpret the issue of the Three-Term President as a discourse that is rejected by many Figures and the public. Republika.co.id seeks to direct the reader to the rejection of the Three-Term President's Discourse